2009
DOI: 10.1002/ppul.20995
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obesity on pulmonary lung function of school aged children in Greece

Abstract: Obesity impacts on many issues of pulmonary medicine, where it is debated if obesity is linked to asthma, atopy or altered lung function tests. Our study aimed to investigate primarily the effect of obesity on the lung function tests and secondary the possible link of obesity with atopy and asthma in a large cohort of children in Greece. Body mass index (BMI) and data from a questionnaire for lung health, atopy, nutritional habits and family history were obtained from 2,715 children aged 6-11 years. Six hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
3
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 41 publications
12
100
3
10
Order By: Relevance
“…Some authors accuse obesity in pathogenesis of asthma while some regard obesity as the outcome and asthma as the risk factor (5). It has been demonstrated that obesity is an important determinant of reduced lung function test results and a risk factor for atopy in children (16). However, it has also been proposed that low energy expenditure due to the inactivity in asthma may be a risk factor for development of obesity (5).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors accuse obesity in pathogenesis of asthma while some regard obesity as the outcome and asthma as the risk factor (5). It has been demonstrated that obesity is an important determinant of reduced lung function test results and a risk factor for atopy in children (16). However, it has also been proposed that low energy expenditure due to the inactivity in asthma may be a risk factor for development of obesity (5).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with other studies Using spirometry tests, Spathopoulos et al 34 investigated the effect of obesity on lung function performance in a large cohort of Greek children aged 6-11 years. Similar to our female adult data, their results indicated that all the pulmonary function parameters, including FEV 1 , FVC, FEV 1 /FVC and FEF 25À75 , were significantly reduced in overweight or obese children compared with normal weight children (P ¼ 0.007, Po0.001, Po0.001 and Po0.001, respectively).…”
Section: Mch Challenge Test and Bmimentioning
confidence: 99%
“…Erişkinlerde yapılan çalışmalarda, genel olarak obezite ile solunum fonksiyon parametrelerinde (özellikle FEV1 ve FVC) azalma saptanmıştır (11)(12)(13)(14)28) . Çocuklardaki sonuçlar çelişkilidir (17,18,(29)(30)(31)(32)(33) . Çalışmamızda obezite ile solunum fonksiyonları arasında anlamlı farklılık saptamadık.…”
Section: İstatistiksel Analizunclassified
“…Bazı çalışmalarda solunum fonksiyon testleri (özellikle FEV1 ve FVC) ile obezite arasında pozitif ilişki bulunmuştur (17,29) . Negatif ilişki saptanan çalışmalarda bulunmaktadır (30,31) . Çalışmamızdaki gibi obezite ile solunum fonksiyonları arasında ilişki saptanmayan çalışmalarda bulunmaktadır (18,32,33) .…”
Section: İstatistiksel Analizunclassified